CARMA3 Is a Critical Mediator of G Protein-Coupled Receptor and Receptor Tyrosine Kinase-Driven Solid Tumor Pathogenesis - McAuley, J. Randall; Freeman, Tanner J.; Ekambaram, Prasanna; Lucas, Peter C.; McAllister-Lucas, Linda M. (Frontiers in Immunology, 2018)
The CARMA-Bcl10-MALT1 (CBM) signalosome, an intracellular protein complex composed of a CARMA scaffolding protein, the Bcl10 linker protein, and the MALT1 protease, was first discovered because the genes encoding its components are targeted by mutation and chromosomal translocation in lymphoid malignancy. We now know that the CBM signalosome plays a critical role in normal lymphocyte function by mediating antigen receptor-dependent activation of the pro-inflammatory, pro-survival NF-B transcription factor, and that deregulation of this signaling complex promotes B-cell lymphomagenesis. More recently, we and others have demonstrated that a CBM signalosome also operates in cells outside of the immune system, including in several solid tumors. In this case, CARMA1 (also referred to as CARD11), which is expressed primarily within hematopoietic cells, is replaced by the more widely expressed CARMA3 (CARD10), and the resultant CARMA3-containing CBM complex operates downstream of specific G protein-coupled receptors (GPCRs) and/or growth factor receptor tyrosine kinases (RTKs). Since inappropriate expression and activation of GPCRs and/or RTKs underlies the pathogenesis of several solid tumors, there is now great interest in elucidating the contribution of CARMA3-mediated cellular signaling in these malignancies. Here, we summarize the key discoveries leading to our current understanding of the role of CARMA3 in solid tumor biology and highlight the current gaps in our knowledge.